Transparency and trust in government: Evidence from a survey experiment - Martin Alessandro; Bruno Cardinale Lagomarsino; Carlos G. Scartascini; Jerónimo Torrealday (Inter-American Development Bank (IDB), 2019)
Does providing information improve citizens' perception about government transparency? Does all information matter the same for shaping perceptions about the government? This paper addresses these questions in the context of an online randomized survey experiment conducted in Argentina. Results show that providing information to citizens matters for shaping perceptions about transparency, and the content of the information matters for affecting the evaluation people make about the government. Those who received a "positive" treatment (showing that the government was over-performing on its promises) increased their trust in the government more than those who received a "negative" treatment (showing that the government was under-performing). The evidence highlights that the channel between transparency and trust may be mediated by the performance of the government.
Keywords: C38; C83; C99; D83; D90; H11; H40; 330; Survey experiments; Information; Beliefs; Trust